1995
DOI: 10.1200/jco.1995.13.10.2524
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of single-agent chemotherapy in low-grade B-cell mucosa-associated lymphoid tissue lymphoma with prominent gastric expression.

Abstract: In low-grade MALT lymphoma with prominent gastric expression, continuous monochemotherapy may constitute an efficient alternative to gastrectomy, regardless of disease stage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
97
0
3

Year Published

1999
1999
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 200 publications
(102 citation statements)
references
References 34 publications
2
97
0
3
Order By: Relevance
“…19,20 In the current study, we confirmed a similar CR rate (89%) in 9 patients including 3 patients with Stage II 1 /IV low-grade lymphoma. In addition, 2 of 3 (67%) patients with DLBL also showed CR after OMC, although 1 of these 2 CR patients later experienced disease recurrence.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…19,20 In the current study, we confirmed a similar CR rate (89%) in 9 patients including 3 patients with Stage II 1 /IV low-grade lymphoma. In addition, 2 of 3 (67%) patients with DLBL also showed CR after OMC, although 1 of these 2 CR patients later experienced disease recurrence.…”
Section: Discussionsupporting
confidence: 85%
“…For OMC, 100 mg/day cyclophosphamide was administered for 6 -12 months. 19,20 For RT, 30 gray (Gy) in 20 fractions (during the course of 4 weeks) was administered to the involved field for low-grade MALT lymphoma, and 40 Gy in 25-27 fractions (5-6 weeks) was administered for MALT lymphoma plus DLBL. [21][22][23] Toxicity of the second-line treatment was graded according to the National Cancer Institute' Common Toxicity Criteria, version 2.0.…”
Section: Second-line Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Regimens include alkylating agents (chlorambucil or cyclophosphamide), which are commonly used in low-grade lymphomas, purine analogs, rituximab, and occasionally anthracycline-based chemotherapy for younger patients with more aggressive disease. French investigators used continuous oral administration of a single alkylating agent [89]. Twenty-four patients were treated with cyclophosphamide or chlorambucil for 12-24 months.…”
Section: Chemoimmunotherapymentioning
confidence: 99%
“…14,15 Several prospective studies have produced encouraging results with chemotherapy, such as cyclophosphamide, chlorambucil, 2-chorodeoxyadenosine (2CdA), and combinations with fludarabine or other drugs. [16][17][18][19][20][21][22] Rituximab, an anti-CD20 monoclonal antibody, has demonstrated activity in patients with recurrent/refractory gastric MALT lymphoma who underwent anti-HP therapy or who were not eligible for anti-HP therapy. [23][24][25] The combination of rituximab with chemotherapy achieved better results that either option separately, similar to the results observed in follicular or diffuse large B-cell lymphoma and without a significant addition of toxicity.…”
mentioning
confidence: 99%